Effect of Traditional Curd Supplementation and Probiotics on Growth Performance and Frequency of Diarrohea in Cattle Calves Under Farmer’s field - Khadda, Balbir Singh; Kanak Lata; Raj Kumar; Khajuria, S.; Aashaq Hussain Dar (Indian Journal of Animal Nutrition, 2021)
A trial was conducted to evaluate the effect of supplementary feeding of curd as probiotics on growth performance and frequency of diarrohea in pre- ruminant cattle calves under farmerâ€™s field in semi- arid condition of central Gujarat, India. Twenty four, pre-ruminant female Gir cattle calves with average age of fifteen days were selected randomly and distributed equally in to four groups, six each in a completely randomized design i.e. T1- basal diet (control), T2 - basal diet + Saccharomyces cerevisiae @ 5 g per calf/ day, T3 - basal diet + Lactobacillus acidophilus @ 1 g (2 x 1010 cfu/ g) per calf/ day and T4 - basal diet + Traditional curd @ 50 mlÂ per calf/ day, respectively for a period of 90 days. The results of the study revealed that the average daily gains and final body weight of calves was significantly (P<0.01) higher in curd and probiotics groups as compared to the control group. The average daily weight gains were statistically higher in curd group (410Â±14.92g) followed by Lactobacillus acidophilus (407Â±15.12g), Saccharomyces cerevisiae (393Â±14.86g) group as compared to control group (301Â±10.74g). There were significant difference in the faecal score between the treatment group and the control after two weeks of the experiment; subsequently, faecal score became constant in the treatment groups and never exceeded the normal value. However, curd and Lactobacillus acidophilus was found to be more effective to control/ reduce the incidence of diarrhea after one weeks of application as compared to Saccharomyces cerevisiae. The incremental B: C Ratio was found to be 5.27, 10.55 and 21.77 in group T2, T3 and T4, respectively which appears to be very lucrative. Based on observations, it may be inferred that the traditionally fermented curd, can effectively be used as a probiotic supplement and has a desirable effect in terms of higher growth rate and checking diarrhea in pre ruminant calves.